(untitled) (Journal of Scientific Research, 2015)
Suppositories are the convenient way of administering drugs in infants. In view of the lack of suitable pediatric antiretroviral formulations in the market, suppositories containing fixed dose combination (FDC) of stavudine, lamivudine and nevirapine (SLN) were developed to allow administration of the correct weight-related dose in pediatric HIV patients as recommended by WHO. Suppositories containing 10 mg of stavudine, 40 mg of lamivudine and 70 mg of nevirapine were prepared by the fusion method using Witepsol H15 semi-synthetic suppository base. All the prepared suppositories were evaluated for various physical parameters like weight variation, melting point, drug content and hardness. The rate and extent of drug release was evaluated using USP apparatus I and samples were analyzed by a validated UV-multicomponent method. The use of surfactants significantly increased the drug release from formulations manufactured with Witepsol H 15 fatty base. The development of pediatric fixed-dose combination formulations represent a new era and mark an important milestone for children living with HIV/AIDS.